Pulmonary effects of inhalation of spark-generated silver nanoparticles in Brown-Norway and Sprague-Dawley rats - Seiffert,J; Buckley,A; Leo,B; Zhu,J; Hussain,F; Guo,C; Warren,J; Hodgson,A; Gong,J; Ryan,M; Zhang,J; Porter,A; et al. (Respiratory Research, 2016)
BackgroundThe increasing use of silver nanoparticles (AgNPs) in consumer products is concerning. Weexamined the potential toxic effects when inhaled in Brown-Norway (BN) rats with a preinflammatorystate compared to Sprague-Dawley (SD) rats.MethodsWe determined the effect of AgNPs generated from a spark generator (mass concentration:600-800 µg/mm3; mean diameter: 13-16 nm; total lung doses: 8 [Low] and 26-28 [High] µg)inhaled by the nasal route in both rat strains. Rats were sacrificed at day 1 and day 7 afterexposure and measurement of lung function.ResultsIn both strains, there was an increase in neutrophils in bronchoalveolar lavage (BAL) fluid at24 hours at the high dose, with concomitant eosinophilia in BN rats. While BAL inflammatorycells were mostly normalised by Day 7, lung inflammation scores remained increasedalthough not the tissue eosinophil scores. Total protein levels were elevated at both lungdoses in both strains. There was an increase in BAL IL-1β, KC, IL-17, CCL2 and CCL3 levels inboth strains at Day 1, mostly at high dose. Phospholipid levels were increased at the highdose in SD rats at Day 1 and 7, while in BN rats, this was only seen at Day 1; surfactantprotein D levels decreased at day 7 at the high dose in SD rats, but was increased at Day 1 atthe low dose in BN rats. There was a transient increase in central airway resistance and intissue elastance in BN rats at Day 1 but not in SD rats. Positive silver-staining was seenparticularly in lung tissue macrophages in a dose and time-dependent response in bothstrains, maximal by day 7. Lung silver levels were relatively higher in BN rat and present atday 7 in both strains.ConclusionsPresence of cellular inflammation and increasing silver-positive macrophages in lungs at day7, associated with significant levels of lung silver indicate that lung toxicity is persistent evenwith the absence of airway luminal inflammation at that time-point. The higher levels andpersistence of lung silve